Fetal reduction, moral permissibility and the all or nothing problem - Wang, Xueshi (Journal of medical ethics, 2023)
There is an ongoing debate about whether multifetal pregnancy reduction from twins to singletons (2-to-1 MFPR) is morally permissible. By applying the all or nothing problem to the cases of reducing twin pregnancies to singletons, Räsänen argues that an implausible conclusion seems to follow from two plausible claims: (1) it is permissible to have an abortion and (2) it is wrong to abort only one fetus in a twin pregnancy. The implausible conclusion is that women considering 2-to-1 MFPR for social reasons ought to abort both fetuses rather than just one. To avoid the conclusion, Räsänen suggests that it is best to carry both fetuses to term and give one for adoption. In this article, I argue that Räsänen’s argument fails for two reasons: the inference from (1) and (2) to the conclusion rests on a bridge principle that does not work in certain circumstances, and there is good reason to reject the claim that it is wrong to abort only one fetus.